Tematsko-konstrukcijski vzorci nastanka in prenovitve stavčnih frazemov - Meterc, Matej (Slavistična revija, 2016)
The author presents a group of (mostly paremiological) propositional phrasemes in which one or more lexical components are a subject of actualization far more frequently than a random lexical component would normally be. While the terms pattern and formula have been mostly used in the past to describe the formation of a larger group of phrasemes with different motivation but based on the same model, the author proposes the term thematic-constructional formula to describe the formation based on actualization of a single paremiological unit. Such examples of phraseological formation were found during the sociolinguistic and corpus- -based research aimed at establishing the Slovene paremiological minimum and optimum.
Keywords: complex pattern model; frazeologija; kompleksni vzorčni model; paremiologija; paremiology; phraseological lemma; phraseology; tematsko-konstrukcijski vzorci; thematic-constructional formula